Nail lesions in a patient with vitiligo - R.V. Saranyuk (Russian Journal of Clinical Dermatology and Venereology, 2026)
Vitiligo is a chronic skin disease of unknown etiology. The appearance of focal depigmentation of various localizations on the skin is its primary clinical manifestation. Vitiligo is considered one of the most common skin diseases. According to various authors, its prevalence ranges from 0.1% to 4%. This dermatosis has a significant impact on the quality of life of patients, especially when the foci of skin depigmentation are localized on visible areas of the body. In addition to the skin, vitiligo can affect hair and mucous membranes. There are data on various nail changes observed in patients with vitiligo. Longitudinal ridges, leukonychia and absence of the lunula are the most common changes in the nail plates. Some authors propose using the term “nail vitiligo” to describe nail lesions in patients with vitiligo. However, proven pathogenetic mechanisms for nail lesions associated with vitiligo have not yet been established. This article presents a clinical case of a patient with vitiligo who exhibited a number of pathological changes in the nail plates. The clinical and dermatoscopic picture, as well as relevant literature data are described.